Performance of Subgrade Soil Blended with Cement and Ethylene Vinyl Acetate. (27th February 2020) - Khan, Kashif Ali; Nasir, Hassan; Alam, Muhammad; Khan, Sajjad Wali; Ahmad, Izhar
Abstract : To improve the essential properties of soil, stabilization proved to be more significant in overcoming the limitations of the desired soil. The improvement of soil properties will not only enhance the mechanical properties rather it will help in preventing dust and erosion formation. In this study, a set of tests are carried out to examine the strength characteristics of subgrade soil blended with ethylene vinyl acetate (EVA) and cement. EVA contributes almost 14% mass to the global waste, requiring bigger lands for its disposal; therefore, in order to promote a green environment and to bring an economical waste management system, an investigation of using EVA in the soil stabilization techniques is attempted. Soil specimens are investigated with and without the inclusion of EVA and cement. For this purpose, EVA was mixed with soil at a percentage level of 3, 6, and 9% whereas the cement was mixed at a percentage level of 4, 6, and 8%. To examine the combined effects of EVA and cement, the specimens were tested for compaction, direct shear, unconfined compression, triaxial, XRD, porosity, and permeability tests. All the soil samples were cured at 7, 14, and 28 days followed by the standard testing procedure. When cement was added to soil up to 4, 6, and 8% at a constant level of EVA (9%), cohesion was increased by 37, 42, and 46% while the unconfined compressive strength (UCS) was increased by 76, 81, and 84% for the same mixes. From the statistics, it clearly evident that the percentage increase caused by the addition of even 3% EVA to the cemented and uncemented soil specimens is very significant regarding cohesion and compressive strength. Porosity and permeability of soil containing both EVA (9%) and cement (8%) were decreased by 37% and 77%, respectively.